2015
DOI: 10.1016/j.cbi.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with human serum butyrylcholinesterase protects Göttingen minipigs exposed to a lethal high-dose of sarin vapor

Abstract: Serum-derived human butyrylcholinesterase (Hu BChE) is a stoichiometric bioscavenger that is being developed as a potential prophylactic nerve agent countermeasure. Previously, we reported the prophylactic efficacy of Hu BChE in Göttingen minipigs against a whole-body exposure to 4.1mg/m(3) of sarin (GB) vapor, which produced lethality over 60min. Since the toxicity of nerve agent is concentration-dependent, in the present study, we investigated the toxic effects of an almost 3-fold higher rate of GB vapor exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…BChE is capable of detoxifying organophosphorous (OP) nerve agents like paraoxon, as well as acetylcholine receptor antagonists, and psychoactive plant alkaloids such as cocaine 2 5 . Exogenously-supplied BChE can augment the bioscavenging capacity of the endogenous enzyme and provide broad protection by sequestering the anticholinesterase agents 6 9 . Moreover, recombinantly-produced BChE variants with improved binding affinities and catalytic prowess can be created to improve on the parameters of the wild type (WT) enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…BChE is capable of detoxifying organophosphorous (OP) nerve agents like paraoxon, as well as acetylcholine receptor antagonists, and psychoactive plant alkaloids such as cocaine 2 5 . Exogenously-supplied BChE can augment the bioscavenging capacity of the endogenous enzyme and provide broad protection by sequestering the anticholinesterase agents 6 9 . Moreover, recombinantly-produced BChE variants with improved binding affinities and catalytic prowess can be created to improve on the parameters of the wild type (WT) enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, BChE (also known as EC3.1.1.8, pseudocholinesterase, nonspecific cholinesterase) is a serine esterase (MW = 345 kDa) comprising four identical subunits containing 574 amino acids, held together by noncovalent bonds, and 36 carbohydrate chains (23.9% by weight) . The efficacy of BChE prophylaxis, in terms of survivability and prevention of cognitive impairment, has been clearly demonstrated in many animal models against multiple LD 50 s of nerve agents and pesticides, and more recently, the ability of HuBChE delivered by intramuscular (IM) injection has been shown to protect against lethal inhaled sarin in minipigs . In Turkey, frozen plasma (containing 3000–5700 units of BChE), given as an alternative or adjunctive treatment with atropine and oximes, has been shown to prevent mortality and intermediate syndrome in acutely insecticide‐exposed and hospitalized individuals …”
Section: Butyrylcholinesterasementioning
confidence: 99%
“…9 The efficacy of BChE prophylaxis, in terms of survivability and prevention of cognitive impairment, has been clearly demonstrated in many animal models against multiple LD 50 s of nerve agents and pesticides, [10][11][12] and more recently, the ability of HuBChE delivered by intramuscular (IM) injection has been shown to protect against lethal inhaled sarin in minipigs. 13 In Turkey, frozen plasma (containing 3000-5700 units of BChE), given as an alternative or adjunctive treatment with atropine and oximes, has been shown to prevent mortality and intermediate syndrome in acutely insecticideexposed and hospitalized individuals. 14 However, because of the limited availability and cost of producing sufficient quantities of plasmaderived HuBChE, focus has switched to the development of a recombinant (r) BChE countermeasure.…”
Section: (Left) In Untreated Individuals Inhaled Ops Transit the Lunmentioning
confidence: 99%
“…1215 Pigs have also been used to evaluate protection against OP nerve agent toxicity afforded by pretreatment with bioscavengers such as HuBChE. 1618 Pharmacokinetic studies showed that the mean residence time of plasma-derived, tetrameric HuBChE in minipigs was 267 h (data not shown), indicating that HuBChE was not rapidly cleared from the circulation of pigs, but remained in the circulation with a half-life similar to that in humans. 19 This suggests a high degree of similarity between human (Hu) and porcine (Po) BChE.…”
Section: Introductionmentioning
confidence: 99%